Access to Credit: Microenterprises in Turkey - Alper Duman (Izmir University of Economics, Department of Economics, 2009)
Access to external finance for small and medium enterprises is vital for survival and growth of such firms. In this paper we have analyzed the determinants of access to credit in microenterprises of Turkey. We use a unique dataset covering a large sample of microenterprises. We find that size and signals of wealth positively affect the likelihood of getting a formal credit.
Keywords: D21; O17; 330; Credit Markets; Informal Firms; Kreditmarkt; KMU; Unternehmensfinanzierung; Türkei